Perception, reality, and optimality: The MSP composite in relation to the farm acts - Pradhan, Mamata; Roy, Devesh; Saroj, Sunil (The Rise, 2020)
Agriculture in India needs to get the markets right, in the first place. Only then can the raising of farmers’ incomes to a reasonable level become a reality. Across space or over time, farmers should be able to trade freely with certainty. If MSP were a panacea, we would not be having any conversation, in the first place, about doubling farmers’ income more than five decades on!